Lupus Eritematosus Sistemik (LES) pada Kehamilan - Suparman, Erna (Universitas Sam Ratulangi, 2021)
Abstract: Systemic lupus erythematosus (SLE) is a multi-organ autoimmune disease that can affect women of childbearing age. Pregnancy causes alterations of the immune and neuroendocrine systems. Moreover, SLE in pregnancy is associated with prematurity and preeclampsia. Confirmation of the SLE diagnosis based on anamnesis, physical examination, and laboratory results is essential to differ the similar symptoms of normal pregnancy from pregnancy with SLE, such as preeclampsia, to lupus nephritis due to differences in treatment. The management of SLE in pregnancy has begun to be well understood; therefore, immunosuppressive drugs can be administered according to the indications and fetal safety. It is essential to educate women with SLE to not get pregnant before the 6-months remission period and explain the relative contraindications to pregnancy.Keywords: systemic lupus erythematosus; pregnancy; immunosuppressiveÂ Â Abstrak: Lupus eritematosus sistemik (LES) merupakan suatu penyakit autoimun multi-organ yang dapat menyerang wanita usia reproduktif. Kehamilan menyebabkan perubahan pada sistem imun dan neuroendokrin. LES pada wanita hamil dihubungkan dengan kejadian kelahiran prematuritas dan preeklamsia. Penentuan diagnosis berdasarkan anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang penting untuk membedakan gejala-gejala yang mirip pada kehamilan normal dengan kehamilan yang disertai LES seperti preeklamsia dengan lupus nefritis karena tatalaksana yang diberikan berbeda. Tatalaksana LES pada kehamilan telah mulai dipahami sehingga pemberian obat-obatan imunosupresif dapat diberikan sesuai dengan indikasi dan keamanan pada janin. Penting untuk mengedukasi wanita dengan LES untuk tidak hamil sebelum melewati masa remisi enam bulan dan menjelaskan kontraindikasi relatif pada kehamilan.Kata kunci: lupus eritematous sistemik; kehamilan; imunosupresif